The Influence of Flash Sales and Free Shipping on Online Purchase Decisions among University Students in Jombang - Nadia Fayza Rohma; Agus Prianto (Journal of Multidisciplinary Science: MIKAILALSYS, 2026)
The rapid growth of e-commerce has encouraged digital platforms to adopt various promotional strategies, including flash sales and free shipping programs, to influence consumer purchase decisions. However, the effectiveness of these promotional tools among university students remains an important area of investigation. This study aims to examine the influence of flash sale and free shipping promotions on online purchase decisions among university students in Jombang Regency. A quantitative approach with a causal-associative design was employed. The study involved 100 respondents selected through proportionate stratified accidental sampling. Data were collected using questionnaires and analyzed through multiple linear regression with IBM SPSS Statistics 27. The findings indicate that flash sale promotions do not have a significant effect on online purchase decisions (Sig. = 0.646 > 0.05), whereas free shipping has a positive and significant effect (Sig. = 0.000 < 0.05). Simultaneously, flash sale and free shipping significantly influence online purchase decisions (F = 63.223; Sig. = 0.000), with a coefficient of determination of 55.4%. These findings suggest that free shipping is a more influential promotional factor than flash sale in shaping students’ online purchase decisions. This study concludes that online purchase decisions among university students are more strongly driven by perceived transaction cost reduction than by time-limited promotional urgency. The findings contribute to the literature on digital marketing and consumer behavior in e-commerce and provide practical implications for e-commerce platforms to prioritize free shipping programs as a more effective marketing strategy for the student consumer segment.